Recurrent Inflammatory Myositis as an Extra-Intestinal Manifestation of Dormant Ulcerative Colitis in a Patient on Long-Term Mesalamine - Srikanth Naramala; Venu Madhav Konala; Sreedhar Adapa; Pravallika Amudala; Romeo C. Castillo; Nikhil Agrawal; Hemant Dhingra (Case Reports in Gastrointestinal Medicine)
Ulcerative colitis (UC) is a chronic systemic inflammatory condition primarily involving the large bowel mucosa with relapsing and remitting episodes. It is also associated with multiple extra-intestinal manifestations [EIM], including skeletal muscle involvement which is rare. Review of the literature reported only a few cases of inflammatory myositis in association with UC. We report an unusual presentation of recurrent inflammatory myositis of lower extremities in a 28-year-old male with quiescent UC and on long-term mesalamine therapy.